Gender role conflicts experienced by Indonesian women with gynecological cancer: A phenomenological study - Atun Raudotul Ma'rifah; Yati Afiyanti; Wisnu Djatmiko; Ida Ruwaida; Ariesta Milanti (Belitung Raya Foundation, Indonesia, 2024)
Background: Gynecological cancer and its treatments can lead to sexual problems, potentially disrupting the gender role performance of women. Sexuality and gender roles are context-specific, yet these issues remain unexplored in the Indonesian context. Objective: This study aimed to explore the gender role conflicts experienced by Indonesian women having gynecological cancer. Method: A qualitative design with a phenomenology approach was utilized in this study. Data were collected through individualized, face-to-face, in-depth interviews conducted from 1 April to 30 December 2022 with 22 women diagnosed with gynecological cancer who had undergone treatments at the Dharmais Cancer Hospital, Jakarta, Indonesia. Data were analyzed using thematic analysis. Results: Three themes were developed: 1) challenges in fulfilling female gender roles after having cancer diagnosis and therapies, 2) emotional struggles related to gender role conflicts, and 3) efforts to cope with gender role conflicts. Conclusion: The study sheds light on how sexual complications due to gynecological cancer and its treatments extend beyond physical issues. A deeper layer of problems around sexual dysfunctions among gynecological cancer survivors is often rooted in traditional gender-role expectations. Nurses should have a comprehensive and contextual understanding of the unique experiences of women living with gynecological cancer to facilitate a positive adaptation to their cancer journey.